2019
DOI: 10.2471/blt.18.223693
|View full text |Cite
|
Sign up to set email alerts
|

Universal health coverage and primary care, Thailand

Abstract: Thailand’s policy on universal health coverage (UHC) has made good progress since its inception in 2002. Every Thai citizen is now entitled to essential preventive, curative and palliative health services at all life stages. Like its counterparts elsewhere, however, the policy faces challenges. A predominantly tax-financed system in a nation with a high proportion of people living in poverty will always strive to contain rising costs. Disparities exist among the different health insurance schemes that provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 29 publications
0
63
0
2
Order By: Relevance
“…Although potential dengue cases have similar febrile symptoms as potential controls (with other conditions), any difference in health-seeking behavior between them may have also biased the results [ 82 ]. Thailand has a universal health coverage program that allows people access to equitable and effective healthcare in primary care centers located in each subdistrict [ 83 , 84 ]. Therefore, by recruiting patients at the main district hospitals, we feasibly captured a high proportion of the febrile patients, including children, living in the area.…”
Section: Discussionmentioning
confidence: 99%
“…Although potential dengue cases have similar febrile symptoms as potential controls (with other conditions), any difference in health-seeking behavior between them may have also biased the results [ 82 ]. Thailand has a universal health coverage program that allows people access to equitable and effective healthcare in primary care centers located in each subdistrict [ 83 , 84 ]. Therefore, by recruiting patients at the main district hospitals, we feasibly captured a high proportion of the febrile patients, including children, living in the area.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2002, despite economic-financial problems and political instability, proper support for UHC has provided Thai citizens with a good level of health services and provisions. Therefore, researchers in this country have tried to disseminate their experiences and practices in the field of UHC to other countries around the world [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Thailand, hailed to have achieved UHC, largely based on general taxation, disparities exist across its three different insurance schemes, which include the civil servants' medical benefit and social security scheme and the universal coverage scheme that includes 72% of the population [51]. The study from Thailand demonstrated that the utilization of new AEDs was highest among those enrolled in the CSMBS scheme (31%), with 19% and 13% of those enrolled in the SSS and NHI schemes respectively received new AEDs.…”
Section: Discussionmentioning
confidence: 99%